2005
DOI: 10.1254/jphs.fmj05002x5
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Significance of T-type Ca2+ Channels: T-type Ca2+ Channels and Drug Development

Abstract: Abstract. T-type Ca2+ channels are present in cardiovascular, neuronal, and endocrine systems; and they are now receiving attention as novel therapeutic targets. Many drugs and compounds non-specificaly block T-type Ca 2+ channels. Certain dihydropyridine compounds, such as efonidipine, have blocking activity on both L-type and T-type Ca 2+ channels which possibly underlies their excellent clinical profiles such as minimum reflex tachycardia and renal protection. Selective inhibitors of T-type Ca 2+ channels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Clinically, T-type Ca 2ϩ channels have represented important therapeutic targets in various types of diseases from cardiovascular diseases, diabetes, and neurological diseases to cancer (Li et al, 2005;Tanaka and Shigenobu, 2005;Panner and Wurster, 2006). Besides their strong association with cardiovascular disease, T-type Ca 2ϩ channels are associated with cancer cell proliferation, and inhibiting T-type Ca 2ϩ channels protects from delayed ischemia-induced damage (Nikonenko et al, 2005).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, T-type Ca 2ϩ channels have represented important therapeutic targets in various types of diseases from cardiovascular diseases, diabetes, and neurological diseases to cancer (Li et al, 2005;Tanaka and Shigenobu, 2005;Panner and Wurster, 2006). Besides their strong association with cardiovascular disease, T-type Ca 2ϩ channels are associated with cancer cell proliferation, and inhibiting T-type Ca 2ϩ channels protects from delayed ischemia-induced damage (Nikonenko et al, 2005).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Besides their strong association with cardiovascular disease, T-type Ca 2ϩ channels are associated with cancer cell proliferation, and inhibiting T-type Ca 2ϩ channels protects from delayed ischemia-induced damage (Nikonenko et al, 2005). T-type Ca 2ϩ channels are also implicated in the pathogenesis of epilepsy and neuropathic pain (Tanaka and Shigenobu, 2005). Thus far, highly selective T-type Ca 2ϩ channel antagonists have not been clinically available.…”
Section: Downloaded Frommentioning
confidence: 99%
“…We have found that efonidipine, a dihydropyridine antihypertensive and antianginal agent, blocks not only the L-type, but also the T-type Ca 2+ channel (8,9), which appear to be related its excellent clinical profile (11). Recently, the R(−)-enantiomer of efonidipine was found to block the T-type Ca 2+ current much more potently than the L-type one based on voltage clamp experiments (12,13).…”
mentioning
confidence: 99%
“…As listed in Table 1, T-type Ca channels exist also in the adrenal and the in vitro experiments using cultured adrenal cells have shown that the T-type CCB suppress the expression of aldosterone synthase gene (CYP11B2) and production of aldosterone (37,38). In harmony with this, clinical studies in healthy subjects and hypertensive patients have shown that the acute or the chronic administrations of T-type CCB lower plasma aldosterone levels (39,40).…”
Section: Calcium Channel Blockers In Antihypertensive Drug Therapy Fomentioning
confidence: 88%